2013
DOI: 10.1017/ppr.2012.1
|View full text |Cite
|
Sign up to set email alerts
|

A Newly Discovered Horse Engraving from La Madeleine (Dordogne), France

Abstract: A new engraving of a horse head has been discovered during a recent re-examination of the Magdalenian osseous projectile point assemblage from La Madeleine curated in the Musée d'Archéologie Nationale (St-Germain-en-Laye, France). Found on one side of an unmodified tip of reindeer tine, this piece was uncovered in amongst a collection of distal (tip) fragments of antler sagaies. While this piece is not unique to La Madeleine – a number of similar pieces having been recovered in early excavations at this site –… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Interestingly, new research on the site sediments has demonstrated that the spears and horse remains were not deposited on dry land, but in the lake under 1-2 metres of water (Urban & Bigga 2015). After 250 ka BP, it is more widely accepted that ambush hunting would have been possible (Stiner 2002) and certainly by the Magdalenian, horse and reindeer were dominant components of the diet (Kuntz & Costamagno 2011), and seem to have been symbolically embedded in Magdalenian lifeways in a way that is not apparent for earlier periods (Langley 2013). An alternative to ambush hunting may be corralling, and even proto-domestication has been discussed for the Solutrean and Magdalenian (Lewis By the early Magdalenian beaver, eel and horse were ubiquitous and probably numerous in Central France and common throughout the area by the middle to late Magdalenian (Table 1).…”
Section: Eel Beaver and Horse Ecologymentioning
confidence: 99%
“…Interestingly, new research on the site sediments has demonstrated that the spears and horse remains were not deposited on dry land, but in the lake under 1-2 metres of water (Urban & Bigga 2015). After 250 ka BP, it is more widely accepted that ambush hunting would have been possible (Stiner 2002) and certainly by the Magdalenian, horse and reindeer were dominant components of the diet (Kuntz & Costamagno 2011), and seem to have been symbolically embedded in Magdalenian lifeways in a way that is not apparent for earlier periods (Langley 2013). An alternative to ambush hunting may be corralling, and even proto-domestication has been discussed for the Solutrean and Magdalenian (Lewis By the early Magdalenian beaver, eel and horse were ubiquitous and probably numerous in Central France and common throughout the area by the middle to late Magdalenian (Table 1).…”
Section: Eel Beaver and Horse Ecologymentioning
confidence: 99%